THE RELATIONSHIP BETWEEN LEARNING INDEPENDENT, LEARNING ENVIRONMENT AT HOME AND SCHOOL LIBRARY USAGE WITH MATHEMATICS LEARNING OUTCOMES - Krisna Nur Septiana; Sunaryo Sunaryo (Universitas Ahmad Dahlan, 2019)
Poor student learning outcomes are associated with many factors. Learning independently, learning environment at home, and school library usage is three factors that allegedly relate to learning outcomes. This study is purposed to determine whether or not a positive and significant correlation of learning independent, learning environment at home, and school library usage to the student's mathematics learning outcomes in the odd semester of eight grade students of Class VIII Junior High School (SMP) Muhammadiyah 1 Minggir Sleman in the academic Year 2017/2018. The sample class in SMP Muhammadiyah 1 Minggir Sleman in 2017/2018 consists of 5class.The class sample is class VIII F, chosen by using a random sampling technique. Data collection techniques used questionnaires and tests. The data collection instrument uses an independent learning questionnaire, a questionnaire of the learning environment at home, school library usage, and a test of learning results. Test of research instrument used validity test, differential test, and reliability test. The prerequisite analysis tests include normality test, linearity test, and independent test. Data analysis for hypothesis testing used simple correlation analysis and multiple regression analysis. The research results show a positive and significant relationship between learning independently, learning environment at home, and school library usage with learning mathematics. At the significant level 5%, dan , with multiple correlation coefficientsÂ and multiple regression equations are three variables . The value of Relative contributionsÂ Â with its double determinant coefficient 0,610 and its effective contribution .